2017
DOI: 10.1161/hypertensionaha.116.08743
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Mitogenic Factor Acts as a Nonclassical Ligand of Calcium-Sensing Receptor, Therapeutically Exploitable for Intermittent Hypoxia-Induced Pulmonary Hypertension

Abstract: Hypoxia-induced mitogenic factor (HIMF) is an inflammatory cytokine playing important role(s) in the development of hypoxic pulmonary hypertension. The molecular target mediating HIMF-stimulated downstream events remains unclear. The coimmunoprecipitation screen identified extracellular calcium-sensing receptor (CaSR) as the binding partner for HIMF in pulmonary artery smooth muscle cells. The yeast 2-hybrid assay then revealed the binding of HIMF to the intracellular, not the extracellular, domain of extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…Previous study has demonstrated that RELM-α induced intracellular calcium release via PLC-IP3 pathway [16] . A recent study found RELM-α has a calcium binding site called CaSR(Ca 2+ -sensing receptor) and induced Ca 2+ influx in a SOCE(store-operated calcium entry) dependent manner [21,36,37] . Intracellular free calcium ([Ca 2+ ]i) is a well known intracellular second messenger involved in the development of cell proliferation [38] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous study has demonstrated that RELM-α induced intracellular calcium release via PLC-IP3 pathway [16] . A recent study found RELM-α has a calcium binding site called CaSR(Ca 2+ -sensing receptor) and induced Ca 2+ influx in a SOCE(store-operated calcium entry) dependent manner [21,36,37] . Intracellular free calcium ([Ca 2+ ]i) is a well known intracellular second messenger involved in the development of cell proliferation [38] .…”
Section: Discussionmentioning
confidence: 99%
“…through extracellular calcium influx in PASMCs [16,21] . To observe the direct effect of RELM-β on cell proliferation and Ca 2+ signaling, we prepared primary cultured PASMCs.…”
Section: Relm-β Promotes Cell Proliferation and Ca 2+ Release In Primmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported as a lung specific growth factor, involving in lung cell proliferation and regulation of compensatory lung growth [27]. HIMF has functions of angiogenic and vasoconstrictive [28]. In lung epithelial cells of mouse, HIMF enhances VEGF production in a PI-3K/Akt-NF-κB signaling pathway-dependent manner [13].…”
Section: Disscussionmentioning
confidence: 99%
“…Zeng et al . () first demonstrated that mitochondrial H 2 O 2 ‐sensitized CaSRs, activated by extracellular Ca 2+ , mediate an increase of hypoxia‐induced Ca 2+ entry and initiates hypoxic pulmonary vasoconstriction. Monocrotaline enhanced the assembly of CaSRs, triggered the mobilization of calcium signalling, damaged pulmonary artery endothelial cells and induced pulmonary hypertension (in rat studies).…”
mentioning
confidence: 99%